Efektifitas metode pembelajaran Kooperatif tipe Komprehensif terhadap hasil evaluasi materi Filosofi Kebidanan - Ernawati Ernawati; Latief Sri Sulistyowati (STIKes Karsa Husada Garut, 2014)
The result of learning evaluation method is affected by several factors which such as learning method. Indicator is a formative test results. Value Midwifery Concept has value unsatisfaction with at average of 60,00. The result of evaluation learning of this research aimed to recognize the effectifity of the cooperatif learning methode in comprehensive type toward the learning evaluation result in the Midwifery Filosofi for the first semester students in STIKes Karsa Husada Garut 2013. The method used in this research is pre-eksperimen design with the research draft one group pre-test post-test design. The population in this research was the first semester students of midwifery program of STIKes Karsa Husada Garut. The writer got the sample for one class with 41 responden whom the writer give the pre-test before the treatment and than they were given the post-test. The data analisys used bivariat with the t-Test dependent (parametric test) with P value=0,0001. The researcher could get the conclution that the cooperatif learning methode in comprehensive type could increse the result learning of the Midwifery Filosofi for student in the first semester in STIKes Karsa Husada Garut. The researcher suggest to use the cooperatif learning method the comprehensive type in learning process which had gained the satisfied result.